(untitled) (Research, Society and Development, 2023)
The aim of this study was to carry out an integrative literature review about the applicability, biocompatibility and efficacy of Mineral Trioxide Aggregate (MTA), in addition to highlighting its importance in clinical dental practice. Medline, Pubmed, Cochrane and Google Scholar search terms, using the following terms: “Dental Pulp Capping”, “Biofunctional Materials” and “Retrograde Obturation”. After applying the inclusion and exclusion criteria, reading the title and abstract, reading the full text, 20 studies were considered to compose this review. Through the related works, I observed that MTA is a bioactive material in which it has good sealing capacity, favoring the formation of less porous, thicker and less traumatic reparative dentin to the pulp tissues, having a low-scale inflammatory effect on the pulp tissue when compared to materials followed for the same purpose. The time of pressure and the way of manipulation and insertion seem to be conflicting factors, however the scope of procedures for its use contributed to its greater clinical use. It is concluded that the choice of MTA in cases of pulpotomy, repair of perforations, direct pulp capping, apical sealing and retrograde obturation presents success rates. However, its long holding period and high cost remained an orderly treatment plan.